2008
DOI: 10.3174/ajnr.a1235
|View full text |Cite
|
Sign up to set email alerts
|

Dose Measurement on Both Patients and Operators during Neurointerventional Procedures Using Photoluminescence Glass Dosimeters

Abstract: BACKGROUND AND PURPOSE:Although radiation skin injuries associated with interventional radiology have been known as a critical issue, there are few reports mentioning direct measurement of the entrance skin dose (ESD). Thus, the purpose of this study was to clarify the regional distributions of ESDs in neurointervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…We reported cumulative skin doses, obtained from the cumulative air kerma at the patient entrance reference point and displayed by most of the modern x-ray systems, 13 while other authors have measured or estimated peak skin doses. [7][8][9][10][11][12][13] Table 2 (adapted by the authors) compares the results reported by several authors. Our cumulative skin doses and DAPs are in the range of other published values.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We reported cumulative skin doses, obtained from the cumulative air kerma at the patient entrance reference point and displayed by most of the modern x-ray systems, 13 while other authors have measured or estimated peak skin doses. [7][8][9][10][11][12][13] Table 2 (adapted by the authors) compares the results reported by several authors. Our cumulative skin doses and DAPs are in the range of other published values.…”
Section: Resultsmentioning
confidence: 99%
“…Our cumulative skin doses and DAPs are in the range of other published values. [7][8][9][10][11][12][13] In 2009, 19 patients (5.9% of the total number of procedures included in the data base during that year) were included in a follow-up program for potential skin injuries. That year, 20 procedures (2 in the same patient) resulted in cumulative skin doses (frontal and lateral planes together) higher than 5 Gy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After their embolisation treatment of small aneurysms, the maximum skin dose was located on the back of the head behind the right ear. Moritake et al [31] extended the study to 32 patients and found maximum skin dose on the back of the head at the level of the ears. Hence, we conclude that the position of maximum skin dose in their study agrees with the positions of our TLD on our 71 patients.…”
Section: Tablementioning
confidence: 98%
“…5 The absorbed doses of organs predict the deterministic risks such as a temporary epilation, hair loss, or opacity of the lens. [6][7][8][9] Previous investigations have indicated a large variation between radiation exposures for cervical and cerebral angiography, depending on the imaged area and the imaging technique used. 2,3,[10][11][12][13][14] A comparison of the radiation exposure between CTA and DSA methods has not been previously performed by using the same dose-measurement setup, to our knowledge.…”
mentioning
confidence: 99%